(untitled) (Revista dos Estudantes de Direito da Universidade de Brasília, 2018)
This essay propose an analysis related to how Warren Court became very particular in American constitutional history by confronting Jim Crow laws, especially by applying the Bill of Rights against States. In this essay, we outline the complexity of the unwritten Constitution after Brown vs Board of Education and other specific contributions of the Warren Court. Cases like Brown vs. Board of Education will be analyzed from a different point of view to understand the Court’s methods and how they affect the comprehension of fundamental rights today beyond what is the constitutional text.